Βιβλιοκρισία: N. SINIOSSOGLOU, Radical Platonism in Byzantium. Illumination and Utopia in Gemistos Plethon, Cambridge(UK), Cambridge University Press, 2011. - ΜΠΑΛΟΓΛΟΥ, Χρήστος (Byzantina Symmeikta, 2013)
ΒΙβλιοκρισία: N. Siniossoglou, Radical Platonism in Byzantium. Illumination and Utopia in Gemistos Plethon, Cambridge(UK), Cambridge University Press, 2011, pp. xvi+454. ISBN 978-1-107-01303-2